Pemblokiran Akses Kredit Akibat Keterlambatan Pelunasan PayLater - Dahlia, Selli; Hazilina, Hazilina; Kurniawan, Heru Yudi (Res Judicata, 2024)
Abstract Fintech companies introduced the Paylater feature, a payment technology with the concept of paying in installments without using a credit card. Paylater is an alternative payment method with an online installment system that does not require a credit card. Paylater from the Traveloka application is one of the financial services supervised by the Financial Services Authority. This research uses a normative law writing method. The data collection used in this study is library research. The data sources used are primary law, secondary law and tertiary law, as well as data collection techniques using legal materials collection techniques such as laws and regulations, doctrines from experts, and online data searches. The results of the study refer to the impact of the delay in completing Paylater on the Traveloka application. The conclusion obtained is that the impact and settlement of the delay that has been approved the terms and conditions are the fines received by the account owner, the loan cost score has decreased, and will be collected by Traveloka. Paying late fines and fees, restricting access using PayLater, getting a declining credit score that can make it difficult for account owners to get loans at banks or other funding companies, these settlements are useful for a deterrent effect for account owners. Keywords: Paylater Traveloka, Transactions, BI-Checking Blacklist.